Novel Selective PPARα Modulator Pemafibrate for Dyslipidemia, Nonalcoholic Fatty Liver Disease (NAFLD), and Atherosclerosis - Shizuya Yamashita; Manfredi Rizzo; Ta-Chen Su; Daisaku Masuda (Metabolites, 2023)
Statins, the intestinal cholesterol transporter inhibitor (ezetimibe), and PCSK9 inhibitors can reduce serum LDL-C levels, leading to a significant reduction in cardiovascular events. However, these events cannot be fully prevented even when maintaining very low LDL-C levels. Hypertriglyceridemia and reduced HDL-C are known as residual risk factors for ASCVD. Hypertriglyceridemia and/or low HDL-C can be treated with fibrates, nicotinic acids, and n-3 polyunsaturated fatty acids. Fibrates were demonstrated to be PPARα agonists and can markedly lower serum TG levels, yet were reported to cause some adverse effects, including an increase in the liver enzyme and creatinine levels. Recent megatrials of fibrates have shown negative findings on the prevention of ASCVD, which were supposed to be due to their low selectivity and potency for binding to PPAR α. To overcome the off-target effects of fibrates, the concept of a selective PPARα modulator (SPPARMα) was proposed. Kowa Company, Ltd. (Tokyo, Japan), has developed pemafibrate (K-877). Compared with fenofibrate, pemafibrate showed more favorable effects on the reduction of TG and an increase in HDL-C. Fibrates worsened liver and kidney function test values, although pemafibrate showed a favorable effect on liver function test values and little effect on serum creatinine levels and eGFR. Minimal drug–drug interactions of pemafibrate with statins were observed. While most of the fibrates are mainly excreted from the kidney, pemafibrate is metabolized in the liver and excreted into the bile. It can be used safely even in patients with CKD, without a significant increase in blood concentration. In the megatrial of pemafibrate, PROMINENT, for dyslipidemic patients with type 2 diabetes, mild-to-moderate hypertriglyceridemia, and low HDL-C and LDL-C levels, the incidence of cardiovascular events did not decrease among those receiving pemafibrate compared to those receiving the placebo; however, the incidence of nonalcoholic fatty liver disease was lower. Pemafibrate may be superior to conventional fibrates and applicable to CKD patients. This current review summarizes the recent findings on pemafibrate.